Semen Leucocytes Affect Sperm Quality of Infertility Patient - Arjadi, Fitranto; Indriani, Vitasari; Siswandari, Wahyu; Priyanto, Edy; Pangestu, Mulyoto (Medical Laboratory Technology Journal, 2022)
The association between the risk factors for male infertility including smoking, obesity, male age, and leukocyte count with sperm analysis, still shows mixed results. This study aims to determine the association between smoking, obesity, male age, and leukocytes count with sperm quality (sperm concentration, sperm motility, and sperm morphology) of infertility patients in Purwokerto. This study is an observational study with a cross-sectional design conducted in the medical records section of the Bunda Arif Hospital Purwokerto. The sample was taken by total sampling. The bivariate test of smoking and obesity behaviour variables with the results of sperm quality using the Chi-Square test and Fisher’s exact test. Male age variables used the Kruskal-Wallis test and the Spearman correlation test. Variable leukocytes count using the Spearman test. The results showed no association between male age, obesity and smoking behaviour with sperm quality, sperm concentration, sperm motility, and sperm morphology (p>0.05). There is a significant association (p<0,05) between leukocyte semen count and spermatozoa concentration, sperm motility, and morphology of spermatozoa. It is concluded that there was a significant association between leukocyte count and sperm quality in infertility patients in Purwokerto. Research needs to be continued by examining the relationship between leukocytopenia and sperm DNA damage by looking at sperm DNA fragmentation.